Prevalence of HBV, HCV, and HIV Infections among Patients Undergoing Hemodialysis in Fasa, Iran: A Six-Year Follow-up Study. - Shamsdin, Seyedeh Azra; Fatahi, Mohamad Reza; Ansari, Ali Reza; Safarpour, Ali Reza (Middle East Journal of Digestive Diseases, 2022)
Background: Hemodialysis (HD) patients are at risk of viral infections such as hepatitis B virus (HBV), hepatitis C virus (HCV), and human immunodeficiency viruses (HIV). Current study aimed to determine the prevalence of HBV, HCV, and HIV among HD patients who attended the dialysis center in Fasa, Iran. Methods: Collectively, 2082 HD patients (1291 men, 791 women) took part in our 6-year follow-up study. Results: 2082 HD patients with a mean age of 56.2 ± 17.8 were included in our study. One (0.09%) patient was HBsAg positive, two (0.18%) patients were anti-HCV positive, and one (0.09%) was anti-HIV positive. There was no significant correlation between the paraclinical parameters of men and women. Conclusion: The present study showed a reduction in the prevalence of HBV, HCV, and HIV infections during 6 years of follow-up in HD patients.